Analisis Pengukuran Kinerja Perusahaan Dengan Menggunakan Metode Balance Scorecard (BSC) Pada Perusahaan Daerah Air Minum (PDAM) Kota Probolinggo - Ratih Nur Cahyanty; H.M Saiful Bahri; Yayuk Indah Wahyuning Tyas (Ecobuss, 2019)
The research was conducted at PDAM (Perusahaan Daerah Air Minum) Probolinggo City with the aim to know the result of company performance analysis by using Balance Scorecard (BSC) method. The type of research used is descriptive quantitative, variable used financial perspective, customer, business / internal, learning and growth perspective. Data used from 2015-2017. The results showed that the financial perspective considered less good because the value of ROE and ROA is still below standard. On the customer perspective is considered good enough because the value of customer acquisition is good, and customer retention is quite good. In Business Internal perspective is considered good because the value of MERR is good. In the learning and growth perspective is considered good because the value of employee retention, training and absenteeism. The performance measurement results from the four Balance Scorecard perspectives are considered good enough. Keywords: Balance Scorecard, Performance Measurement Company.